Legal Protection of Workers' Rights Against Cases of Unilateral Termination of Employment in Review of Law No. 6 of 2023 on Labour Copyright - Wijaya, Dion Untung; Kurniati, Yeti; Durahman, Dani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to find out the protection of workers' rights for unilateral termination of employment (PHK) carried out by the company. specifically aims to find out: first, how is the form of legal protection of the rights of workers / labourers who experience unilateral termination of employment (PHK) carried out by the company based on Law Number 6 of 2023 concerning Job Creation, second, how can legal remedies be taken by workers / labourers who experience termination of employment (PHK) who are not fulfilled their rights by the employer. This research uses normative juridical legal research methods with a statue approach and conceptual approach. The results of this study indicate that in the event of termination of employment (PHK) has a legal regulatory basis listed in Article 151 of the Job Creation Law which discusses the ways to terminate employment (PHK). Exceptions regarding termination of employment (PHK) are contained in Article 153 of the Job Creation Law. Various reasons for termination of employment (PHK) can be done but not done in a unilateral manner by the company which will harm workers/labourers. Legal protection against unilateral termination of employment (PHK) has been regulated in Article 153 of the Job Creation Law, where in the termination of employment (PHK), the company will be responsible for the termination of employment (PHK).